Gender Issues in the Built Environment: A Study on the Role of Architecture for a Sustainable Society - Ceylan, Salih (2022)
Societies are sustainable if they consist of a mixture of users with various interests, needs, and abilities. Sustainable societies are defined as structures that include different elements in a balance to remain healthy over the long term. One of the key elements of a sustainable society is gender equality. It can be maintained through various factors where architectural design and the built environment can become effective instruments. Although the role of architecture in gender issues is sometimes ignored, its reflection can be seen in the built environment in many different instances. Therefore, architecture has the responsibility to remark gender issues in the built environment to aid in meeting the needs of a sustainable society. This paper presents a study that examines the importance and the role of architectural design in a sustainable society through gender equality in the built environment. The hypothesis of the paper states that the built environment is perceived differently by women and men, and it needs to be designed accordingly. The methodology consists of a literature review on the relationship of gender and architecture, and a quantitative analysis of a questionnaire conducted in Istanbul, Turkey among women and men. Outcomes of the study reveal that gender equality in the built environment and gender equality in the society have a mutual relationship, so that architecture needs to consider them as primary input data in design